Serosurveillance of Orientia tsutsugamushi and Rickettsia typhi in Bangladesh. - Maude, R; Maude, R; Ghose, A; Amin, MR; Islam, M; Ali, M; Bari, MS; Majumder, M; Tanganuchitcharnchai, A; Dondorp, A; Paris, D; Bailey, R; et al. (American Society of Tropical Medicine and Hygiene, 2014)
Scrub and murine typhus infections are under-diagnosed causes of febrile illness across the tropics, and it is not known how common they are in Bangladesh. We conducted a prospective seroepidemiologic survey across six major teaching hospitals in Bangladesh by using an IgM enzyme-linked immunosorbent assay. Results indicated recent exposure (287 of 1,209, 23.7% seropositive for Orientia tsutsugamushi and 805 of 1,209, 66.6% seropositive for Rickettsia typhi). Seropositive rates were different in each region. However, there was no geographic clustering of seropositive results for both organisms. There was no difference between those from rural or urban areas. Rickettsia typhi seroreactivity was positively correlated with age. Scrub typhus and murine typhus should be considered as possible causes of infection in Bangladesh.